2014
DOI: 10.2172/1163822
|View full text |Cite
|
Sign up to set email alerts
|

Iodine adsorption on ion-exchange resins and activated carbons: batch testing

Abstract: Among radioactive contaminants, iodine-129 (129 I) is commonly either the top or among the top risk drivers, along with technetium-99 (99 Tc), at radiological waste disposal sites and contaminated groundwater sites where nuclear material fabrication or reprocessing has occurred. Radioactive iodine (129 I) is of environmental concern due to its long half-life (1.6 × 10 7 years), toxicity, and mobility in the environment (Councell et al. 1997). However, there are currently very few approaches that effectively ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 4 publications
(6 reference statements)
0
21
0
Order By: Relevance
“…refs. [8] and [9]), this approach only removes iodide and not iodate, offering a tool for the separation between the two iodine species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…refs. [8] and [9]), this approach only removes iodide and not iodate, offering a tool for the separation between the two iodine species.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to notice that iodine can exist in several forms even at the same time. Further, the speciation of iodine affects essentially its geochemical behaviour and interactions with natural materials [5][6][7] or synthetic solid sorbents developed for iodine removal [8,9]. To reliably assess the interaction of different remediation materials, it is essential to precisely control and survey the speciation of iodine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a plethora of potential adsorbents, both natural and synthetic, including activated carbon (e.g., Hoskins et al 2002;Parker et al 2014;Kosaka et al 2012;Ikari et al 2015), zeolites (e.g., Li et al 2014), layered double hydroxides (e.g., Kentjono et al 2010;Theiss et al 2014), organoclays (e.g., Li et al 2014), argentite (e.g., Li et al 2014;Kaplan et al 2000;Mattigod et al 2007), aerogels (e.g., Sánchez-Polo et al 2006, self-assembled monolayers on mesoporous silica (SAMMS) (e.g., Mattigod et al 2007;Kaplan et al 2000), carbon nanotubes (e.g., Pishko et al 2013), and a number of other materials. Some of these adsorbents include silver impregnation (doping) to promote iodine capture and formation of immobile silver iodide when adsorbed.…”
Section: Ex Situ Aqueous Adsorptionmentioning
confidence: 99%
“…ABEC resin development for large-scale chromatographic equipment has been undertaken (Bond et al 1999;Alexandratos 2009). Batch testing (Parker et al 2014) of ion exchange on synthetic resin media for iodine treatment has shown adsorption rates similar to those for certain activated carbon media, on the order of 1.7 µg iodine per gram of resin. Reduction of iodine to iodide in the testing by Parker et al (2014) was found to more than double the loading capacity of most resins (except Dowex 21K and SIR-700).…”
Section: Ex Situ Ion Exchangementioning
confidence: 99%